The impact of Inflation and Unemployment on Economic Growth in Jordan: AN ARDL Bounds Testing Approach - Hussain, Majeed Ali; Saaed, Afaf Abdull J. (Archives of Business Research, 2018)
This paper examines the effect of inflation (INFR) and unemployment rate (UNR) on economic growth which is measured by Gross Domestic Product (RGDP) in percent on in Jordan for the period 1976-2016. To achieve this objective unit root, Augmented Dickey Fuller test was used. Subsequently, the Autoregressive distributed Lag ( ARDL) bounds testing approach and Error Correction Model (ECM-ARDL) model are applied to examine the both long-run and short-run causality issues between the variables under consideration. The empirical results of the study revealed, the results of the unit root test indicate that Real Gross Domestic Product growth (RGDPG), unemployment and inflation are tested at first difference then the problem of unit root has disappeared and hence they have become stationary at first difference. The bounds tests suggest that the variables of interest are bound together in the long-run when RGDPG is the dependent variable. Also, there is a long run relationship amongst the variables when INFR is the dependent variable. The results indicate also that there is no significant Granger causality from INFR to UNR and from RGDPG to UNR and from RGDPG to INFR and from INFR to RGDPG as well the short run. The results of this study can be used by all respected authorities in Jordan, especially authorities of economic and social institutions, so that they could attempt to reduce and control unemployment and inflation to achieve economic growth.